A high-capacity positive electrode lead paste for lead-acid batteries and a preparation method thereof
By using high-capacity cathode lead paste in lead-acid batteries and using carbon nanotubes and lanthanum doped carriers to improve the composite utilization rate of lead oxide and lead sulfate, the problems of low specific energy and short service life of lead-acid batteries have been solved, and achieved High capacity and high stability lead-acid batteries.
Patent Information
- Application Number
- CN202411627091.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Lead-acid batteries have low specific energy and short service life, mainly due to the low utilization rate of positive electrode materials, it is difficult for the prior art to effectively improve their capacity and service life.
A high-capacity positive electrode lead paste for lead-acid batteries is used, which includes lead powder, high-capacity additives, red lead, stannous sulfate and sulfuric acid. The high-capacity additives are composed of carbon nanotubes, nitric acid solution, tri(N,N''- It is prepared from materials such as diisopropylformamide (diisopropylformamide) lanthanum and anhydrous dimethylacetamide, and forms a doping carrier through hydrothermal and roasting processes to improve the composite utilization rate of lead oxide and lead sulfate.
The high capacity and long life of lead-acid batteries are achieved. The initial specific capacity reaches more than 180mAh/g, and the capacity retention rate after 300 cycles is about 90%, which significantly improves the performance of the battery.
Smart Images

Figure CN119133371B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead-acid batteries, and in particular, relates to a high-capacity positive electrode lead paste for lead-acid batteries and a preparation method thereof. Background Art
[0002] Lead-acid battery is a storage battery whose electrodes are mainly made of lead and its oxides, and whose electrolyte is sulfuric acid solution. In the discharge state, the main component of the positive electrode is lead dioxide, and the main component of the negative electrode is lead. In the charging state, the main components of the positive and negative electrodes are both lead sulfate. Although its mass-to-energy and volume-to-energy cannot be compared with lithium batteries, it is cheap, simple in structure, has good high-current discharge performance, and has no memory effect. It is widely used in power supplies for electric bicycles, electric vehicles, etc., starting power supplies for automobiles, ships, tanks, etc., and backup power supplies for power plants, automatic control systems, etc.
[0003] However, the low specific energy and short service life of lead-acid batteries seriously restrict the application of lead-acid batteries. The main reason is that the utilization rate of positive electrode materials is not high. There are two main technical means to increase the capacity of lead-acid batteries in the prior art. One is to use synthesis technology, such as preparing lead oxide with nanostructure as positive electrode material, improving the utilization rate by refining the particle size, or synthesizing lead oxide with specific shapes to increase the specific surface area, such as sea urchin shape, flower shape, etc., which can improve the specific capacity of positive electrode materials to a certain extent. However, this type of method is costly and contrary to the low-cost application concept of lead-acid batteries; the second is to compound additives, mainly conductive materials, among which carbon materials are the most widely used. However, this type of additive itself cannot increase the specific capacity, but can only increase the conductivity of the positive electrode material. Excessive addition will seriously reduce the specific capacity. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a high-capacity positive electrode lead paste for a lead-acid battery and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A high-capacity positive lead paste for a lead-acid battery, comprising the following raw materials in parts by weight:
[0007] 100 parts of lead powder, 5.5-7.2 parts of high-capacity additive, 3.5-4.5 parts of red lead, 0.15-0.2 parts of stannous sulfate and 10-13 parts of sulfuric acid;
[0008] The high capacity additive is prepared by the following method:
[0009] Step A1: Mix the carbon nanotubes and nitric acid solution, add them and disperse them by ultrasonic, heat them to 80-90°C, stir them at 240-360 rpm for 2-3 hours, remove the liquid phase by centrifugation, wash and dry them to obtain an activated carrier;
[0010] Furthermore, the solid-liquid mass ratio of the carbon nanotubes to the nitric acid solution is 1:20-25, the concentration of the nitric acid solution is 4-6 mol / L, and the carbon nanotubes are treated with nitric acid to generate a large number of active groups on the surface, thereby improving the loading capacity of the carbon nanotubes.
[0011] Furthermore, the diameter of the carbon nanotube is no greater than 50 nm.
[0012] Step A2: Mix tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide under dry nitrogen protection, heat to 40-55°C, add activated carrier and ultrasonically vibrate for 20-30 minutes, stand for 12 hours, centrifuge and dry, and then calcine at 900°C for 2 hours under nitrogen protection to obtain a doped carrier;
[0013] Furthermore, the usage ratio of the activated carrier, tris(N,N''-diisopropylformamide)lanthanum and anhydrous dimethylacetamide is 10g:0.12-0.16g:20-30mL. The activated carrier has good adsorption properties. Tris(N,N''-diisopropylformamide)lanthanum is loaded by adsorption, and lanthanum doping is formed on the activated carrier after calcination.
[0014] Step A3: grind lead oxide, lead sulfate and sulfuric acid solution into slurry, add doping carrier and mix, heat to 65-80°C, slowly add concentrated sulfuric acid under ultrasonic stirring to react for 1.5-2h, centrifuge and remove liquid phase, vacuum dry and transfer to a nitrogen atmosphere furnace for roasting at 600°C for 3h, grind and crush the material to obtain a high-capacity additive;
[0015] Furthermore, the dosage ratio of lead oxide, lead sulfate, doping carrier, sulfuric acid solution and concentrated sulfuric acid is 0.1 mol: 0.05 mol: 1.5-2.2 g: 20-25 mL: 5-8 mL, the mass fraction of sulfuric acid solution is 40%, and lead oxide and lead sulfate form tetrabasic lead sulfate in sulfuric acid and are compounded with the doping carrier.
[0016] A method for preparing a high-capacity positive lead paste for a lead-acid battery comprises the following specific operations: mixing lead powder, a high-capacity additive, red lead and stannous sulfate in a high-speed mixer, transferring the mixture into a paste mixer, adding sulfuric acid and mixing the mixture, and obtaining the high-capacity positive lead paste.
[0017] Furthermore, the fineness of the lead powder is not less than 200 mesh.
[0018] Furthermore, the mass fraction of sulfuric acid in the raw material is 35-40%.
[0019] Beneficial effects of the present invention:
[0020] The invention discloses a high-capacity additive for lead-acid batteries. The additive takes carbon nanotubes as a matrix, generates a large number of active groups on the surface through nitric acid treatment, improves the adsorption of the carbon nanotubes, activates the carbon nanotubes, utilizes the adsorption characteristics of the carbon nanotubes, adsorbs and loads tri(N,N''-diisopropylformamide)lanthanum in a liquid phase environment, forms lanthanum doping on the activated carrier after roasting, and forms tetrabasic lead sulfate composite on the surface of the doped carrier through hydrothermal and roasting processes. The high-capacity additive itself contains a large amount of tetrabasic lead sulfate, which has a certain positive significance for improving the capacity and service life of lead paste. The carbon nanotubes compounded therein have microscopic hollow gaps, form ion channels in the charge and discharge process of the lead-acid battery, are conducive to the full embedding and de-embedding of ions, make full use of active substances, and show higher specific capacity in tests. The lanthanide doped on the tube wall of the carbon nanotubes inhibits the growth of lead oxide and lead dioxide, keeps the ion channels formed by the carbon nanotubes stable, and shows higher cycle stability in tests. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0022] Figure 1 Electron microscope image of the doped carrier prepared in Example 4 of the present invention:
[0023] Figure 2 The graph is a cycle capacity curve of the positive lead paste of the present invention applied to a lead-acid battery. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1, preparing high-capacity positive lead paste for lead-acid batteries, the specific implementation process is as follows:
[0026] (1) Preparation of high-capacity additives
[0027] Step A1: Mix carbon nanotubes and nitric acid solution, disperse them ultrasonically at 20kHz, heat them to 80°C, and stir them at 240rpm for 3h, wherein the carbon nanotubes are CNT104 products of Beijing Dekedaojin Technology Co., Ltd. with a tube diameter of 10-20nm, the concentration of the nitric acid solution is 4mol / L, and the solid-liquid mass ratio of the carbon nanotubes to the nitric acid solution is 1:25. Then, centrifuge to remove the liquid phase and wash and dry to obtain an activated carrier.
[0028] Step A2: Take tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide and mix them under the protection of dry nitrogen, heat to 40°C, add an activated carrier and ultrasonically oscillate at 28kHz for 30 minutes, let it stand for 12 hours, then centrifuge and dry, and then calcine at 900°C for 2 hours under the protection of nitrogen, wherein the amount ratio of the activated carrier, tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide is 10g:0.16g:30mL, to obtain a doped carrier.
[0029] Step A3: grind lead oxide, lead sulfate and sulfuric acid solution to make a slurry, add a doping carrier to mix, heat to 65°C, slowly add concentrated sulfuric acid under ultrasonic stirring to react for 2 hours, centrifuge and remove the liquid phase, vacuum dry and transfer to a nitrogen atmosphere furnace and roast at 600°C for 3 hours, wherein the amount ratio of lead oxide, lead sulfate, doping carrier, sulfuric acid solution and concentrated sulfuric acid is 0.1 mol: 0.05 mol: 1.5 g: 20 mL: 8 mL, the mass fraction of sulfuric acid solution is 40%, grind and crush the material to obtain a high-capacity additive.
[0030] (2) Configuration of positive electrode lead paste
[0031] Ingredients: 100 parts of lead powder, battery-grade lead powder from Chaowei Power Group Co., Ltd., with a fineness of 200 mesh; 5.5 parts of high-capacity additive, homemade in this embodiment; 4.5 parts of red lead, battery-grade raw material; 0.15 parts of stannous sulfate, industrial-grade raw material; 10 parts of sulfuric acid, 35% by mass of industrial-grade raw material.
[0032] Paste preparation: Add lead powder, high-capacity additive, red lead and stannous sulfate into a high-speed mixer, stir and mix at 1200 rpm for 10 minutes, then transfer the mixture into a paste mixer, add sulfuric acid and mix for 1 hour to prepare a high-capacity positive electrode lead paste.
[0033] Example 2, preparing high-capacity positive electrode lead paste for lead-acid batteries, the specific implementation process is as follows:
[0034] (1) Preparation of high-capacity additives
[0035] Step A1: Mix carbon nanotubes and nitric acid solution, disperse them ultrasonically at 25kHz, heat them to 90°C, and stir them at 360rpm for 2h, wherein the carbon nanotubes are CNT106 products of Beijing Dekedaojin Technology Co., Ltd. with a tube diameter of 30-50nm, the concentration of the nitric acid solution is 6mol / L, and the solid-liquid mass ratio of the carbon nanotubes to the nitric acid solution is 1:20. Then, centrifuge to remove the liquid phase and wash and dry to obtain an activated carrier.
[0036] Step A2: Take tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide and mix them under the protection of dry nitrogen, heat to 55°C, add an activated carrier and ultrasonically oscillate at 33kHz for 20 minutes, let it stand for 12 hours, then centrifuge and dry, and then calcine at 900°C for 2 hours under the protection of nitrogen, wherein the amount ratio of activated carrier, tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide is 10g:0.12g:20mL, to obtain a doped carrier.
[0037] Step A3: grind lead oxide, lead sulfate and sulfuric acid solution to make a slurry, add a doping carrier to mix, heat to 80°C, slowly add concentrated sulfuric acid under ultrasonic stirring to react for 1.5h, centrifuge and remove the liquid phase, vacuum dry and transfer to a nitrogen atmosphere furnace and roast at 600°C for 3h, wherein the amount ratio of lead oxide, lead sulfate, doping carrier, sulfuric acid solution and concentrated sulfuric acid is 0.1mol: 0.05mol: 2.2g: 25mL: 5mL, the mass fraction of sulfuric acid solution is 40%, grind and crush the material to obtain a high-capacity additive.
[0038] (2) Configuration of positive electrode lead paste
[0039] Ingredients: 100 parts of lead powder, battery-grade lead powder from Chaowei Power Group Co., Ltd., with a fineness of 200 mesh; 7.2 parts of high-capacity additive, homemade in this embodiment; 3.5 parts of red lead, battery-grade raw material; 0.2 parts of stannous sulfate, industrial-grade raw material; 13 parts of sulfuric acid, 40% by mass of industrial-grade raw material.
[0040] Paste preparation: Add lead powder, high-capacity additive, red lead and stannous sulfate into a high-speed mixer, stir and mix at 1200 rpm for 10 minutes, then transfer the mixture into a paste mixer, add sulfuric acid and mix for 1 hour to prepare a high-capacity positive electrode lead paste.
[0041] Example 3, preparing high-capacity positive lead paste for lead-acid batteries, the specific implementation process is as follows:
[0042] (1) Preparation of high-capacity additives
[0043] Step A1: Mix carbon nanotubes and nitric acid solution, disperse them ultrasonically at 25kHz, heat them to 85°C, and stir them at 300rpm for 2.5h, wherein the carbon nanotubes are CNT105 products of Beijing Dekedaojin Technology Co., Ltd. with a tube diameter of 20-30nm, the concentration of the nitric acid solution is 5mol / L, and the solid-liquid mass ratio of the carbon nanotubes to the nitric acid solution is 1:22. Then, centrifuge to remove the liquid phase and wash and dry to obtain an activated carrier.
[0044] Step A2: Take tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide and mix them under the protection of dry nitrogen, heat to 45°C, add an activated carrier and ultrasonically oscillate at 33kHz for 25 minutes, let it stand for 12 hours, then centrifuge and dry, and then calcine at 900°C for 2 hours under the protection of nitrogen, wherein the amount ratio of the activated carrier, tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide is 10g:0.14g:30mL, to obtain a doped carrier.
[0045] Step A3: grind lead oxide, lead sulfate and sulfuric acid solution to make a slurry, add a doping carrier to mix, heat to 75°C, slowly add concentrated sulfuric acid under ultrasonic stirring to react for 1.6 hours, centrifuge and remove the liquid phase, vacuum dry and transfer to a nitrogen atmosphere furnace and roast at 600°C for 3 hours, wherein the amount ratio of lead oxide, lead sulfate, doping carrier, sulfuric acid solution and concentrated sulfuric acid is 0.1 mol: 0.05 mol: 1.8 g: 25 mL: 6 mL, the mass fraction of sulfuric acid solution is 40%, grind and crush the material to obtain a high-capacity additive.
[0046] (2) Configuration of positive electrode lead paste
[0047] Ingredients: 100 parts of lead powder, battery-grade lead powder from Chaowei Power Group Co., Ltd., with a fineness of 200 mesh; 6.5 parts of high-capacity additive, homemade in this embodiment; 4.2 parts of red lead, battery-grade raw material; 0.17 parts of stannous sulfate, industrial-grade raw material; 12 parts of sulfuric acid, 40% by mass of industrial-grade raw material.
[0048] Paste preparation: Add lead powder, high-capacity additive, red lead and stannous sulfate into a high-speed mixer, stir and mix at 1200 rpm for 10 minutes, then transfer the mixture into a paste mixer, add sulfuric acid and mix for 1 hour to prepare a high-capacity positive electrode lead paste.
[0049] Example 4, preparing high-capacity positive electrode lead paste for lead-acid batteries, the specific implementation process is as follows:
[0050] (1) Preparation of high-capacity additives
[0051] Step A1: Mix carbon nanotubes and nitric acid solution, disperse them ultrasonically at 20kHz, heat them to 80°C, and stir them at 360rpm for 2.2h, wherein the carbon nanotubes are CNT104 products of Beijing Dekedaojin Technology Co., Ltd. with a tube diameter of 10-20nm, the concentration of the nitric acid solution is 5mol / L, and the solid-liquid mass ratio of the carbon nanotubes to the nitric acid solution is 1:25. Then, centrifuge to remove the liquid phase and wash and dry to obtain an activated carrier.
[0052] Step A2: Take tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide and mix them under the protection of dry nitrogen, heat to 45°C, add an activated carrier and ultrasonically oscillate at 28-33kHz for 30 minutes, stand for 12 hours, centrifuge and dry, and then calcine at 900°C for 2 hours under the protection of nitrogen, wherein the amount ratio of activated carrier, tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide is 10g:0.15g:25mL, to obtain a doped carrier.
[0053] Step A3: grind lead oxide, lead sulfate and sulfuric acid solution to make a slurry, add a doping carrier to mix, heat to 70°C, slowly add concentrated sulfuric acid under ultrasonic stirring to react for 1.9 hours, centrifuge and remove the liquid phase, vacuum dry and transfer to a nitrogen atmosphere furnace and roast at 600°C for 3 hours, wherein the amount ratio of lead oxide, lead sulfate, doping carrier, sulfuric acid solution and concentrated sulfuric acid is 0.1 mol: 0.05 mol: 2 g: 25 mL: 6 mL, the mass fraction of sulfuric acid solution is 40%, grind and crush the material to obtain a high-capacity additive.
[0054] (2) Configuration of positive electrode lead paste
[0055] Ingredients: 100 parts of lead powder, battery-grade lead powder from Chaowei Power Group Co., Ltd., with a fineness of 200 mesh; 6.7 parts of high-capacity additive, homemade in this embodiment; 4 parts of red lead, battery-grade raw material; 0.18 parts of stannous sulfate, industrial-grade raw material; 13 parts of sulfuric acid, 35% by mass of industrial-grade raw material.
[0056] Paste preparation: Add lead powder, high-capacity additive, red lead and stannous sulfate into a high-speed mixer, stir and mix at 1200 rpm for 10 minutes, then transfer the mixture into a paste mixer, add sulfuric acid and mix for 1 hour to prepare a high-capacity positive electrode lead paste.
[0057] Comparative Example 1
[0058] This comparative example is a control example of Example 4, except that the high-capacity additive is replaced with 6.2 parts of battery-grade tetrabasic lead sulfate and 0.5 parts of carbon nanotubes CNT105, and the rest of the implementation process is exactly the same.
[0059] Comparative Example 2
[0060] This comparative example is a control example of Example 4, except that the high-capacity additive is replaced with 6.2 parts of battery-grade tetrabasic lead sulfate and 0.5 parts of carbon nanofibers, and the rest of the implementation process is exactly the same.
[0061] The positive electrode lead paste prepared above was manually coated on the board and grid, with the amount of paste applied being 1.3 g / cm 2 After compaction, immerse it in 40% sulfuric acid for 5 seconds. After draining, place it in a steam curing kettle for 3 hours, and then immerse it in an electrolytic cell to form a positive electrode plate.
[0062] The externalized negative electrode plate produced by Chaowei Power Co., Ltd. was assembled into a battery with the positive electrode plate prepared above and the AMG separator, and 1.2 g / cm 2 The sulfuric acid solution is used as the electrolyte to assemble a lead-acid battery.
[0063] The lead-acid battery above was tested on a multi-channel battery tester. Capacity test: charging voltage was 2.5V, discharging voltage was 1.8V, and the initial capacity of the positive lead paste was measured; cycle life test: cyclic charging and discharging was performed under 100% DOD conditions, and the discharge capacity was detected after 300 cycles. The capacity retention rate was calculated as (discharge capacity after cycle / initial capacity) × 100%; the specific test data are shown in the following table:
[0064]
[0065] From the test results in the above table, it can be seen that the initial specific capacity of the positive electrode lead paste prepared in Example 4 reaches more than 180 mAh / g, and the capacity retention rate after 300 cycles of 100% DOD is about 90%, which has high capacity and high stability characteristics compared with the comparative example; Based on the above test results, the doped carrier prepared in Example 4 was observed by electron microscopy, as shown in detail Figure 1 , and provide the cycle capacity curve of the above lead-acid battery, as shown in the following figure: Figure 2 .
[0066] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
Claims
1. A high-capacity positive electrode lead paste for lead-acid batteries, characterized in that: The following raw materials are included in parts by weight: 100 parts of lead powder, 5.5-7.2 parts of high-capacity additive, 3.5-4.5 parts of red lead, 0.15-0.2 parts of stannous sulfate and 10-13 parts of sulfuric acid; The high capacity additive is prepared by the following method: Step A1: Mix the carbon nanotubes and nitric acid solution, add them and disperse them by ultrasonic, heat them to 80-90°C, stir them at 240-360 rpm for 2-3 hours, remove the liquid phase by centrifugation, wash and dry them to obtain an activated carrier; Step A2: Mix tri(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide under dry nitrogen protection, heat to 40-55°C, add activated carrier and ultrasonically vibrate for 20-30 minutes, stand for 12 hours, centrifuge and dry, and then calcine at 900°C for 2 hours under nitrogen protection to obtain a doped carrier; Step A3: Grind lead oxide, lead sulfate and sulfuric acid solution into slurry, add doping carrier and mix, heat to 65-80°C, slowly add concentrated sulfuric acid under ultrasonic stirring to react for 1.5-2h, centrifuge and remove the liquid phase, transfer to a nitrogen atmosphere furnace after vacuum drying and roast at 600°C for 3h, grind and crush the material to obtain a high-capacity additive.
2. The high-capacity positive electrode lead paste for lead-acid batteries according to claim 1, characterized in that: The solid-liquid mass ratio of the carbon nanotubes to the nitric acid solution is 1:20-25, and the concentration of the nitric acid solution is 4-6 mol / L.
3. The high-capacity positive electrode lead paste for lead-acid batteries according to claim 2, characterized in that: The diameter of carbon nanotubes is no greater than 50 nm.
4. The high-capacity positive electrode lead paste for lead-acid batteries according to claim 3, characterized in that: The usage ratio of the activated carrier, tris(N,N''-diisopropylformamido)lanthanum and anhydrous dimethylacetamide is 10g:0.12-0.16g:20-30mL.
5. The high-capacity positive electrode lead paste for lead-acid batteries according to claim 4, characterized in that: In step A3, the usage ratio of lead oxide, lead sulfate, doping carrier, sulfuric acid solution and concentrated sulfuric acid is 0.1 mol: 0.05 mol: 1.5-2.2 g: 20-25 mL: 5-8 mL, and the mass fraction of sulfuric acid solution is 40%.
6. The high-capacity positive electrode lead paste for lead-acid batteries according to claim 1, characterized in that: The fineness of lead powder shall not be less than 200 mesh.
7. The high-capacity positive electrode lead paste for lead-acid batteries according to claim 1, characterized in that: The mass fraction of sulfuric acid in the raw material is 35-40%.
8. The method for preparing a high-capacity positive lead paste for a lead-acid battery according to any one of claims 1 to 7, characterized in that: The specific operation is: mix the lead powder, high-capacity additive, red lead and stannous sulfate in a high-speed mixer, transfer them into a paste making machine, add sulfuric acid and mix them, and obtain a high-capacity positive electrode lead paste.
Citation Information
Patent Citations
Method for preparing lithium iron phosphate serving as positive active material of lithium battery
CN101814600A
Method for leaching cobalt in lithium battery by combining NCNTs (Nitrogen-doped Carbon Nanotubes) modified electrode and microorganism
CN108390118A